Peran Orang Tua Dalam Pengenalan Pengetahuan Gender Anak Usia Dini Pada Masa Pandemi - Listyaningrum, Eunike Milasari (Satya Widya, 2021)
Parents have an important role in introducing knowledge about gender to early childhood. The introduction of gender knowledge is given by parents to children because it is related to development and formation of behavior and personality of children in the future. This study aims to determine the parents’ role in the introduction of gender in early childhood during the pandemic. This study used descriptive qualitative research method. The characteristics of subjects in this study were parents who had children at an early age range of 4-6 years. Data were collected through observation, interview, and documentation techniques. The results of this study show that parents have an important role in introducing gender knowledge to early childhood, especially during current pandemic.